2011
DOI: 10.1007/s13197-011-0511-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparative antioxidant effect of aqueous extracts of curry leaves, fenugreek leaves and butylated hydroxytoluene in raw chicken patties

Abstract: Antioxidant properties and use of aqueous extracts of curry leaves (Murraya koenigii) and fenugreek leaves (Trigonella foenum-graecum) as source of natural antioxidant in raw chicken meat were evaluated. Four treatments viz., I. Control (meat +2% salt), II.BHT (meat +2% salt +0.1% BHT), III. CLE (meat +2% salt +2% curry leaves extract) and IV. FLE (meat +2% salt +2% fenugreek leaves extract) were compared for lipid oxidation during eight days refrigerated storage. The average phenolic content was 59.2 and 52.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 23 publications
3
14
0
1
Order By: Relevance
“…The radical scavenging activity of different herbs evaluated in the study was more or less within the range reported in the literature (Abbasi et al, ; Al‐Juhaimi & Ghafoor, ; Basak et al, ; Devatkal et al, ; Gruyal, ; Gul et al, ; Jaiswal et al, ; Pawar, ; Rahman et al, ; Sonara & Saralaya, ). However, some deviations might be attributed to variations in chemical composition of the different herbs with respect to phenolics and other antioxidants as well as pro‐oxidants content (Bouayed & Bohn, ; Fukumoto & Mazza, ; Kaur & Mondal, ; Sengul, Yildiz, Gungo, Cetin, & Eser, ; Tupe, Kemse, & Khaire, ).…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…The radical scavenging activity of different herbs evaluated in the study was more or less within the range reported in the literature (Abbasi et al, ; Al‐Juhaimi & Ghafoor, ; Basak et al, ; Devatkal et al, ; Gruyal, ; Gul et al, ; Jaiswal et al, ; Pawar, ; Rahman et al, ; Sonara & Saralaya, ). However, some deviations might be attributed to variations in chemical composition of the different herbs with respect to phenolics and other antioxidants as well as pro‐oxidants content (Bouayed & Bohn, ; Fukumoto & Mazza, ; Kaur & Mondal, ; Sengul, Yildiz, Gungo, Cetin, & Eser, ; Tupe, Kemse, & Khaire, ).…”
Section: Resultssupporting
confidence: 79%
“…The total phenolics content of different herbs evaluated in the study was more or less within the range reported in the literature (Abbasi, Khodadadi, Tavilani, & Goodarzi, ; Al‐Juhaimi & Ghafoor, ; Basak, Mallick, Mazumder, & Verma, ; Devatkal, Thorat, Manjunatha, & Anurag, ; Gruyal, ; Gul, Ahmad, Kondapi, Qureshi, & Ghazi, ; Jaiswal, Patel, Saxena, & Naik, ; Pawar, ; Rahman et al, ; Sonara & Saralaya, ). However, some deviations might be attributed to variations variety of the herbs (Abdulkadir, Zawawi, & Jahan, ; Benabdallah, Rahmoune, Boumendjel, Aissi, & Messaoud, ; Wangcharoen & Gomolmanee, ), prevailing agroclimatic conditions of the area in which herb is grown (Jaiswal et al, ), agronomic practises followed in the herb farming (Azhar, Hussain, Ashraf, & Abbasi, ; Pakade, Cukrowska, & Chimuka, ), maturity of the herb at the stage of harvesting (Jinesh, Jaishree, Badami, & Shyam, ), method followed for postharvest processing of the herb (Al‐Juhaimi & Ghafoor, ; Pakade et al, ; Vijayalakshmi & Shourie, ), the type and concentration of solvent (Gul et al, ; Hasim, Falah, Ayunda, & Faridah, ; Wangcharoen & Gomolmanee, ) as well as polarity of solvent (Basak et al, ; Rahman et al, ;) used for analysis, the method followed for the estimation of the total phenolics content (Jinesh et al, ; Rahman et al, ; Wangcharoen & Gomolmanee, ), etc.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…20,21 This seed also has a hypoglycaemic activity due to the presence of alkaloids, flavonoids, salicylate, nicotinic acid and polyphenols. 15 In India, curry leaf is used as a traditional spice in many food preparations. There is also a practice of using curry leaf in folk medicine for treating different metabolic and infectious diseases.…”
Section: Resultsmentioning
confidence: 99%
“…14 Gum acacia, fenugreek (Trigonella foenum-graecum L) seeds, curry leaf (Murraya koenigii) and aloe vera (Aloe barbadensis) gel are common hypoglycaemic and antioxidant rich ingredients. [15][16][17][18][19][20][21] The edible coatings that have been used in the study are natural and so are considered safe. It is envisaged that coating the foxtail millet with these edible substances may improve the glycemic index (GI) along with its keeping quality, nutritional value and antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%